Meso-Mono-[4-(1, 4, 7-triazacyclononanyl)]-tri(phenyl)]porphyrin and the respective zinc(ii)-complex: complete characterization and biomolecules binding abilities. Issue 4 (4th April 2016) - Auras, Bruna L.; Oliveira, Vanessa A.; Terenzi, Hernán; Neves, Ademir; Iglesias, Bernardo A.
Abstract : We aimed to synthesize a new series of triazacyclononanyl-porphyrins (4 and5 ) with the potential ability to bind DNA. Abstract : We aimed to synthesize a new series of triazacyclononanyl-porphyrins (4 and5 ) with the potential ability to bind DNA. For this, the free-base porphyrin4 and the corresponding Zn(ii )-complex5 were synthesized by the Schiff base formation reaction. The binding ability of the porphyrin derivatives4 and5 with DNA from calf-thymus was studied by UV-vis and emission spectroscopy. Detailed analysis of the results suggests that the interaction of these systems most probably occurs through π-stacking and secondary hydrogen interaction surface binding with ct-DNA. Moreover, we also demonstrate the substantial ability of porphyrins4 and5 to generate 1 O2 and to photocleave plasmid DNA after irradiation.